2009
DOI: 10.1111/j.1743-6109.2008.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Phosphodiesterase Type 5 Inhibitors

Abstract: Introduction Phosphodiesterase type 5 (PDE5) inhibitors are widely used as first-line therapy for erectile dysfunction (ED). Their efficacy and safety combined with an increasing understanding of cyclic guanosine monophosphate (cGMP)-regulated mechanisms have triggered a number of attempts to determine their effects on the cardiovascular system and their potential benefits in cardiovascular conditions. Aim To review and discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 114 publications
(154 reference statements)
2
48
0
6
Order By: Relevance
“…Clinical trials and postmarketing data of all PDE5 inhibitors have demonstrated the drugs to be safe in patients with CV disease. Thus, no increase in myocardial infarction rates has been ob- (Vlachopoulos et al, 2009). No PDE inhibitor has adversely affected total exercise time or time to ischemia during exercise testing in men with stable angina.…”
Section: Drugs For Nonintracavernosal Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials and postmarketing data of all PDE5 inhibitors have demonstrated the drugs to be safe in patients with CV disease. Thus, no increase in myocardial infarction rates has been ob- (Vlachopoulos et al, 2009). No PDE inhibitor has adversely affected total exercise time or time to ischemia during exercise testing in men with stable angina.…”
Section: Drugs For Nonintracavernosal Administrationmentioning
confidence: 99%
“…The duration of interaction between organic nitrates and PDE inhibitors varies according to the PDE inhibitor and the nitrate. If a patient develops angina while using a PDE inhibitor, other antiangina agents may be used instead of nitroglycerin or until the appropriate time has passed (24 h for sildenafil or vardenafil and 48 h for tadalafil) (Vlachopoulos et al, 2009).…”
Section: Drugs For Nonintracavernosal Administrationmentioning
confidence: 99%
“…There are numerous studies suggesting that phosphodiesterase-5 (PDE-5) inhibitors, which are the first-line therapy of ED, might be effective in reversing generalized endothelial dysfunction [6]. Acute treatment with PDE-5 inhibitors showed favorable effects on brachial artery flow-mediated dilatation up to 24 h post-dose in men with [7] and without ED [8] and in patients with coronary artery disease [9] and chronic heart failure [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chronic treatment restores endothelium-dependent relaxations at various sites of the vascular tree, even up to one week after cessation of the treatment [11]. Beneficial acute (sildenafil, vardenafil) and chronic (sildenafil) effects of PDE-5 inhibitors on aortic stiffness and wave reflections in men with ED are also well-known [6,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[1,7] Furthermore, recent studies have shown VDN as an effective agent in penile rehabilitation, decreasing lower urinary tract symptoms from benign prostatic hyperplasia and management of pulmonary hypertension. [5,8,9] The side effects of VDN are the same as with other PDE-5 inhibitors, such as nausea, abdominal pain, abnormal vision, hypotension, tachycardia and rare heart attack. Physicians should advise patients to stop using PDE-5 inhibitors and seek immediate medical attention in the event of a side effect as a safety measure.…”
Section: Introductionmentioning
confidence: 99%